Tanggapan Kenabian atas Nubuat Yang Gagal. Studi Teologis-Eksegetis atas Yesaya 56-66 - V. Indra Sanjaya (Jurnal Orientasi Baru, 2009)
Prophet and prophecy are common terminologies in the worlds religions. Aprophet is normally understood as a person sent by God to deliver a messageto the people concerning the future events. Therefore, a prophets words claimsto have divine quality. A big problem would then arouse when a prophecy (orprophecies) uttered by person claimed to be Gods prophet fails to materialize.This paper tries to critically analyze the common response to the problem ofunfulfilled prophecy, which consists of a blaming-the-other strategy, and offersfresh responses to such a problem based on an exegetical work on the thirdpart of the Book of Isaiah, namely Isa 56-66.